The Effectiveness Of The Farmer Card Program In The Distribution Of Subsidized Fertilizers At The Agricultural Office Of The Agricultural Extension Center (BPP) Work Unit Of Jampangkulon District, Sukabumi Regency - Wanti Alvini Pamungkas; Dine Meigawati; Andi Mulyadi (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The Farmer Card is a transaction tool in the form of debit cards such as ATMs that function as a means to redeem subsidized fertilizers. This research focuses on the effectiveness of the Farmer Card Program in distributing subsidized fertilizers in Jampangkulon District, Sukabumi Regency. This research began with the discovery of several problems including uneven distribution of subsidized fertilizers because there are still many farmers who do not get subsidized fertilizer balances, then farmers complain that they do not understand how to apply the Farmer Card, and finally EDC machines that often error so that they can hinder transactions. The theory used to measure and know about how effective the Farmer Card Program is using the theory proposed by Duncan (1973: 274-275). The method used in this study is a qualitative method with a descriptive qualitative approach. The results in this study show that the Farmer Card Program has not been effective because the main purpose of the Card is to prosper and facilitate farmers in redeeming subsidized fertilizers, but in fact farmers still feel burdened, especially for farmers over the age of 40 years who are not tech-savvy. Then there are still many obstacles that occur, especially the problem of EDC machines as a means of fertilizer redemption transactions often errors because the network in Jampangkulon District is not yet stable. Keywords: Effectiveness, Farmer Card Program, Subsidized Fertilizer Distribution